Statistical analysis of travelling ionospheric disturbances during geomagnetic storms - Mothibi, Matsobane Alex (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This thesis presents observations of medium to large-scale traveling ionospheric disturbances (TIDs) originating from high latitudes, and propagating towards the equator and TIDs originating from the equator with a poleward propagation in the African-European sector during geomagnetically disturbed conditions between 2006 and 2022. 196 TID activities propagating over the African-European sector were observed, of these TID activities, 161 and 33 were observed during geomagnetic storms, and simultaneous occurrence of geomagnetic storms and solar flares, respectively. Total electron content perturbations derived from Global Navigation Satellite Systems (GNSS) observations within a latitude range of 40Â°S"“60Â°N and longitude ranges of 20Â°-40Â°E representing the African-European sector were analysed based on the storm criteria of Dst â‰¤ -30 nT. The GNSS total electron content (TEC) data were used to obtain the two dimensional (2d) TEC perturbations. The northern hemispheric part of the African sector has limited data coverage which is visualized by a gap around 20Â°, where there were no data coverage can be observed in the 2d TEC maps. An important result is that large-scale TIDs (LSTIDs) and medium-scale TIDs (MSTIDs) were found to occur predominantly during the main and recovery phases of geomagnetic storms respectively, at least over the African-European sector. During the main phase of storms equatorward LSTID activity was relatively consistent across both hemispheres, with years of solar maximum, between 2013 and 2015, showing higher frequencies of events. Equatorward MSTID activity appeared less frequent overall, particularly in the southern hemisphere (SH), suggesting that equatorward LSTID activity are more prominent during the main phase of geomagnetic storms. Poleward TID activity were more predominant in the recovery phase than the main phase of geomagnetic storms.
Keywords: Sudden ionospheric disturbances; Geomagnetic storm; Solar flares; Global Positioning System; Gravity waves